Role Participation: A Comparison across Age Groups in a Norwegian General Population Sample - Tore Bonsaksen (Hindawi-Wiley, 2018)
Background. Life events, illness, and disability may alter a person's role participation, in which case occupational therapy may be an appropriate intervention. However, role participation data derived from the general population, which is required for meaningful comparison, is largely missing. This study is aimed at describing past, present, and anticipated role participation in a general population sample from Norway and at examining differences in current role participation between age groups. Methods. In 2015, a sample of 140 persons (age range 19-94 years, 65% females) from the Norwegian general population completed the Role Checklist at one occasion. The data were analyzed descriptively and with chi-square tests and one-way analysis of variance. Results. The most frequent role was a home maintainer (93.6%), and the least frequent was a religious participant (7.1%). Participants aged 65 years and above had fewer roles compared with their younger counterparts and had to a larger extent experienced role loss over the course of their lives. Conclusions. Role continuity was the most prevalent role pattern in the total sample, whereas role loss appeared to be the most prevalent role pattern among those in the oldest age group. Rehabilitation services in general and participation-focused occupational therapy in particular may profit from assessing role participation in clients and potentially target roles through intervention.